Earliest Christianity - Hengel, Martin; Bowden, John (London, UK SCM, 1979)
Includes bibliographical references and index.
Compilation of "Acts and the history of earliest Christianity" (translation of Zur urchristlichen Geschichtsschreibung, Stuttgard, Calwer Verlag, 1979) and "Property and riches in the early church" (translation of Eigentum und Reichtum in der fruhen Kirche, Stuttgard, Calwer Verlag, 1973)
Keywords: Church history -- primitive and early church -- ca. 30-600.; Bible N.T. Acts -- criticism, interpretation, etc; Bible N.T. Acts -- history of contemporary events